Differential effects of targeting Notch receptors in a mouse model of liver cancer. Issue 3 (28th January 2015) - Huntzicker, Erik G.; Hötzel, Kathy; Choy, Lisa; Che, Li; Ross, Jed; Pau, Gregoire; Sharma, Neeraj; Siebel, Christian W.; Chen, Xin; French, Dorothy M.
Abstract : Primary liver cancer encompasses both hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA). The Notch signaling pathway, known to be important for the proper development of liver architecture, is also a potential driver of primary liver cancer. However, with four known Notch receptors and several Notch ligands, it is not clear which Notch pathway members play the predominant role in liver cancer. To address this question, we utilized antibodies to specifically target Notch1, Notch2, Notch3, or jagged1 (Jag1) in a mouse model of primary liver cancer driven by v‐akt murine thymoma viral oncogene homolog and neuroblastoma RAS viral oncogene homolog (NRas). We show that inhibition of Notch2 reduces tumor burden by eliminating highly malignant HCC‐ and CCA‐like tumors. Inhibition of the Notch ligand, Jag1, had a similar effect, consistent with Jag1 acting in cooperation with Notch2. This effect was specific to Notch2, because Notch3 inhibition did not decrease tumor burden. Unexpectedly, Notch1 inhibition altered the relative proportion of tumor types, reducing HCC‐like tumors but dramatically increasing CC‐like tumors. Finally, we show that Notch2 and Jag1 are expressed in, and Notch2 signaling is activated in, a subset of human HCC samples. Conclusions : These findings underscore the distinct roles of different Notch receptors in the liver and suggest that inhibition of Notch2 signaling represents a novel therapeutic option in the treatment of liver cancer. (Hepatology 2015;61:942–952)